Marko Damjanović1*, Darko Guljaš1 , Miroslava Polovinski-Horvatović1 , Borislav Iliĉić1 , Saša Krstović1 , Marko Vukadinović1 , Kristijan Cokoski2 , Dejan Beuković1 - Marko Damjanović, Darko Guljaš, Miroslava Polovinski-Horvatović, Borislav Iliĉić, Saša Krstović, Marko Vukadinović, Kristijan Cokoski, Dejan Beuković (University of Novi Sad, Faculty of Agriculture, Novi Sad, Serbia, 2025)
The Nature Park Begeĉka jama, a branch of the Danube River, represents a significant natural asset, serving as a habitat and breeding ground for various fish species, and other aquatic and terrestrial organisms. It is located in an environment of intensive agriculture, where there is a potential issue of watercourse pollution with heavy metals originating from phosphate fertilizers and pesticides. Since heavy metals are major water pollutants that accumulate in sediments, water, and the aquatic food chain, their presence in this ecosystem could pose a serious threat to aquatic organisms and, consequently, to human health. Since no data are available on metal contamination levels in fish on this location, the aim was to investigate the occurrence of two metals (cadmium (Cd) and lead (Pb)) measured in two organs (gills and liver) from two fish species that illustrate different ecological niches: largemouth bass (Micropterus salmoides) and gibel carp (Carassius gibelio). The selection of these species was based on differences in feeding and behavior during winter. Gibel carp, an omnivore, burrows into sediment during winter, increasing exposure to pollutants, while carnivorous largemouth bass slows its metabolism and retreats to deeper, warmer waters with minimal feeding activity. A total of 22 fish were analyzed, with 11 individuals from each species. Since two organs were examined per fish, this resulted in a total of 44 samples, which were analyzed by graphite furnace atomic absorption spectrometry. The concentration of Pb in the liver of largemouth bass was below the LOQ in 81.81% of samples, with only two positive detections (45.8 and 78.03 µg/kg) while in gibel carp, it ranged from 47.38 to 669.1 µg/kg (100% detected), with a median level of 263.1 µg/kg. In the gills, Pb concentration in largemouth bass varied from 15.39 to 3640 µg/kg (63.64% was below LOQ), whereas in gibel carp, it ranged from 211.8 to 612.6 µg/kg (100% detected), with a median level of 398.5 µg/kg. There was no significant difference in Pb levels between the organs of gibel carp (p>0.05). Regarding Cd, its concentration in the liver of largemouth bass ranged from 23.74 to 43.14 µg/kg, with a median level of 28.18 µg/kg and 54.55% of samples below LOQ, while in gibel carp, it ranged from 15.82 to 401.7 µg/kg, with a median level of 96.99 µg/kg and 36.36% of samples below LOQ. In the gills, Cd was detected only in largemouth bass, with a concentration of 56.77 µg/kg, whereas all gibel carp samples had Cd levels below LOQ. The results show that Pb accumulation was proportionally higher in gibel carp compared to largemouth bass, suggesting that gibel carp may serve as a more reliable biomarker for Pb contamination. On the other hand, findings indicate that the liver is a better biomarker for chronic cadmium exposure, since Cd showed a different distribution, with a higher detection frequency in the liver of both species. The observed metal concentrations are in agreement with previous analyses of water and sediment from the studied locations, which showed that Cd and Pb levels in water were below the LOQ, while in sediment, Pb ranged from 0.47 to 30.5 µg/kg and Cd was either below the LOQ or detected up to 0.37 µg/kg.
Keywords: cadmium, fish, GFAAS, lead, Serbia